Rediscovering the region: the West German daily press in the 1970s - Haase, Christian; Kraiker, Christian-W. (Oxford University Press, 2017)
After Willy Brandt’s Ostpolitik, West Germans began to accept the more permanent division of the country and rediscovered the regional fundaments of their federal political system. A catalyst for this process was provided by a massive regionalization of the daily press in the aftermath of the recession in 1973. That regionalization entailed the delineation of new regional distribution and advertising areas, the launch of new editions, the growth of regularly and irregularly published alternative papers and a stronger emphasis on regional news. In the 1970s regionalization cut across all segments of the market and across party affiliations and affected established papers, the irregular alternative press and even television and broadcasting. It propelled the West German daily press to its height point in German history, with more than 25 million copies per day in 1982. The new regional focus of the daily press increased public awareness of regional protests, regional identity politics and regional scandals during the chancellorship of Helmut Schmidt (1974–82) to such an extent that the article concludes that the 1970s were not only a ‘global’ decade, but also a regional decade. The history of the regional press that is presented in the article for the first time facilitates a new view of regional changes in economic prosperity, criticism of the federal state and the emergence of regional consumer markets between 1974 and 1982. The analysis provides a cornerstone for a more detailed media history of the Bonn Republic and a new understanding of the 1970s.